Wnt/β-Catenin Regulates the Activity of Epiprofin/Sp6, SHH, FGF, and BMP to Coordinate the Stages of Odontogenesis - Aurrekoetxea, Maitane; Irastorza, Igor; García-Gallastegui, Patricia; Jiménez-Rojo, Lucia; Nakamura, Takashi; Yamada, Yoshihiko; Ibarretxe, Gaskon; Unda, Fernando J. (Frontiers in Cell and Developmental Biology, 2016)
Background: We used an in vitro tooth development model to investigate the effects of overactivation of the Wnt/β-catenin pathway during odontogenesis by bromoindirubin oxime reagent (BIO), a specific inhibitor of GSK-3 activity. Results: Overactivatingthe Wnt/β-catenin pathway at tooth initiation upregulated and ectopically expressed the epithelial markers Sonic Hedgehog (Shh), Epiprofin (Epfn) and Fibroblast growth factor8 (Fgf8), which are involved in the delimitation of odontogenic fields in the oral ectoderm. This result indicated an ectopic extension of the odontogenic potential. During tooth morphogenesis, Fibroblast growth factor4 (Fgf4), Fibroblast growth factor10 (Fgf10), Muscle segment homeobox 1 (Msx-1), Bone Morphogenetic protein 4 (Bmp4) and Dickkopf WNT signaling pathway inhibitor 1 (Dkk-1) were overexpressed in first molars cultured with BIO. Conversely, the expression levels of Wingless integration site 10b (Wnt-10b) and Shh were reduced. Additionally, the odontoblast differentiation markers Nestin and Epfn showed ectopic overexpression in the dental mesenchyme of BIO-treated molars. Moreover, alkaline phosphatase activity increased in the dental mesenchyme, again suggesting aberrant, ectopic mesenchymal cell differentiation. Finally, Bmp4 downregulated Epfn expression during dental morphogenesis. Conclusions: We suggest the presence of a positive feedback loop wherein Epfn and β-catenin activate each other. The balance of the expression of these two molecules is essential for proper tooth development. We propose a possible link between Wnt, Bmp and Epfn that would critically determine the correct patterning of dental cusps and the differentiation of odontoblasts and ameloblasts.